Nano-Messengers of the Heart: Promising Theranostic Candidates for Cardiovascular Maladies - Yedavilli, Sneha; Singh, Anula Divyash; Singh, Damini; Samal, Rasmita (Frontiers in Physiology, 2022)
Till date, cardiovascular diseases remain a leading cause of morbidity and mortality across the globe. Several commonly used treatment methods are unable to offer safety from future complications and longevity to the patients. Therefore, better and more effective treatment measures are needed. A potential cutting-edge technology comprises stem cell-derived exosomes. These nanobodies secreted by cells are intended to transfer molecular cargo to other cells for the establishment of intercellular communication and homeostasis. They carry DNA, RNA, lipids, and proteins; many of these molecules are of diagnostic and therapeutic potential. Several stem cell exosomal derivatives have been found to mimic the cardioprotective attributes of their parent stem cells, thus holding the potential to act analogous to stem cell therapies. Their translational value remains high as they have minimal immunogenicity, toxicity, and teratogenicity. The current review highlights the potential of various stem cell exosomes in cardiac repair, emphasizing the recent advancements made in the development of cell-free therapeutics, particularly as biomarkers and as carriers of therapeutic molecules. With the use of genetic engineering and biomimetics, the field of exosome research for heart treatment is expected to solve various theranostic requirements in the field paving its way to the clinics.